Does ownership structure improve financial reporting quality? Evidence of real earnings manipulation among Pakistani firms - Shah, Syed Farhan; Abdul Rashid,; Malik, Wasim Shahid; Shahzad, Faisal (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines whether ownership structure improve the financial reporting quality. We built on two different econometric techniques including Feasible Generalized Least Square (FGLS) and Panel Corrected Standard error Model (PCSE) by using a sample of 150 non-financial firms listed on Pakistan Stock exchange for the period of 2008- 2017. The results propose that institutional ownership and as well as managerial ownership are negatively related to real earnings manipulation, which implies that both these types of ownership structure act as a best monitoring mechanism in reducing real earnings manipulation and thus enhancing the financial reporting quality. Whereas, state ownership and family ownership are positively associated to real earnings manipulation, which suggest that family and state ownerships engage in real earnings manipulation and thus reducing the financial reporting quality. Overall results supports the alignment hypothesis, entrenchment effect and efficient monitoring hypothesis of the agency theory. The results of the study provide practical implication for investors and policymakers in understanding the role of ownership on financial reporting quality.